Computational Analysis of Fighter Aircraft Wing under Mach Number 0.7 for Small Sweep Angles - Srinivas, G.; Potti, Srinivasa Rao (Applied Mechanics and Materials, 2014)
Fighter aircraft wings are the leading lift generating components for any aerospace vehicle. The recital of any flying vehicle largely depends on its wing design. Missiles and the fighter aircrafts which are having propulsion system mostly have fins to control and maneuver. In this present paper work an attempt has been made to design a fighter aircraft wing configuration which will be used in some air launched air to surface guided weapons fighter aircraft. The main focus of this paper agreement in determining the Sweep-back effects on fighter aircraft wing under transonic condition at different angles of attack (AoA) from 0 to 5 degrees. For this the fighter aircraft wing performance for various flow conditions and sweep angles are obtained based on the empirical, semi-empirical and CFD simulation results. Hence by studying these computational results would help in the optimizing geometry for better performance, an finest wing design for the air launched air to surface body with conservative wing can be obtained.